Kepemimpinan Bupati Abdul Hadi di Kabupaten Jember Tahun 1968-1979 - Bhre Widyaloka Mertowijoyo; Ratna Endang Widuatie (Program Studi Ilmu Sejarah Fakultas Ilmu Budaya Universitas Jember, 2021)
This study discusses the leadership of Regent Abdul Hadi in Jember Regency in 1968-1979. With the aim of knowing how Abdul Hadi's leadership was for two periods. This writing uses psychology to help provide an overview of the influence of individuals on the form and course of leadership. Leadership theory is used to analyze Abdul Hadi's form of leadership. This study employed a historical method consisting of heuristics, source criticism, interpretation, and historiography. Before becoming regent, he had a military background that influenced his leadership path. Abdul Hadi was elected Regent of Jember Regency by acclamation in 1968 when he served as Dandim 0824 Jember. The results showed that Abdul Hadi's paternalistic leadership style was used for two periods in regional development, this style was fatherly who always guided his subordinates. A friendly attitude and good communication between leaders and the community encouraged the development programs to be easier to implement. For example, in the construction of the Jami' Al Baitul Amien Mosque in Jember, the plan to build this mosque came from Abdul Hadi's desire to have a mosque that could accommodate the community for the next 5 years, but the funds at that time were insufficient. To overcome this, Abdul Hadi issued a policy to invite the whole community to work together in development, until in 1976 this development was completed. Another example of major development is the construction of the Gajah Mada to Kaliwates double way road. This development also involved the community in it, from joint discussions to the voluntary eviction of community houses. With the developments that have been carried out, Jember Regency has obtained facilities and better quality of life of the community